Financial Management Efficiency Strategy in the Boarding House UMKM Sector - Sifa, Rizkika Astha; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
This article aims to analyze the financial management strategies implemented at Kost Gabriela to achieve operational efficiency and tenant satisfaction. This study focuses on operational cost management, cash flow control, and competitive rental pricing. Data were collected through interviews with boarding house owners and tenants, as well as direct observation for three months. The analysis was conducted qualitatively to identify patterns in financial management strategies. The results showed that controlling operational costs, including facility maintenance, efficient energy use, and cooperation with local partners, successfully increased efficiency without reducing service quality. Competitive pricing strategies also contributed to tenant satisfaction levels. However, inadequate internet access is a major challenge, reducing tenant comfort and potentially affecting the competitiveness of boarding houses amid the increasing need for stable internet connections. Overall, this study confirms that effective financial management strategies can create a balance between cost efficiency and customer satisfaction, which ultimately supports the sustainability of Kost Gabriela's business. Improvements in internet infrastructure are recommended to increase competitiveness and maintain tenant loyalty.